A spam rejection scheme during SMTP sessions based on layer-3 e-mail classification - Marsono, Muhammad Nadzir (Elsevier Ltd., 2009)
This paper proposes a scheme that rejects spam e-mails during their simple mail transfer protocol (SMTP) sessions. This scheme utilizes a layer-3 e-mail classification technique, which allows e-mail classes to be estimated before the end of SMTP sessions at receiving e-mail servers. We analyze the proposed scheme using discrete-time Markov chain analysis under varying e-mail traffic loads and service capacities. This paper also considers the effects of e-mail retransmission and illegal spam relaying by zombie systems on the performance of the proposed scheme. Results from our analysis show that e-mail server loading decreases by using the proposed technique. This allows the reduction in non-spam e-mail queuing delays and loss probability. Our scheme also protects e-mail servers from being overloaded by spam traffic and, if performed collectively over the Internet, it is capable of performing outbound spam control.